Upaya Peningkatan Kinerja Petugas Apron Movement Control (AMC) Dalam Menunjang Keamanan dan Keselamatan Penerbangan di Bandar Udara Internasional Supadio Pontianak - Octhaviani; Ika Fathin Resti Martanti (Journal of Creative Student Research, 2023)
Apron movement control personnel must have a license or competency certificate to prevent human error from occurring due to negligence of personnel at work. Drivers who drive GSE vehicles exceeding the maximum limit do not know the rules on the Air side, officers who do not wear vests when on the apron, and taxi way charie under repair. This study aims to determine the performance of Apron Movement Control (AMC) officers in supporting flight security and safety at Supadio Pontianak International Airport, to find out the obstacles encountered by Apron Movement Control (AMC) officers. In supporting flight safety and security at Supadio Pontianak Airport, and to find out the efforts made to improve the performance of AMC officers in supporting flight safety and security at Supadio Pontianak Airport. In conducting research, the author uses qualitative research methods, which aim to find, analyze and manage data obtained from direct events that occur in the field by understanding social interactions through interviews and observations. This research was conducted at PT. Angkasa Pura II (persero) Supadio Pontianak International Airport at the Apron Movement Control (AMC) Unit from 01 January 2023 to 30 January 2023. Data analysis techniques used in this study include: data reduction, data display and conclusions. The results of this study indicate that the AMC unit at Supadio Pontianak International Airport has been very good at supporting flight safety and security as seen from the personnel. Actions to overcome safety and security risks that are implemented in the work environment of the AMC unit are implemented by plotting parking stands and coordination with towers and GH. The obstacles encountered by the AMC unit included the lack of Apron Movement Control unit personnel, as well as the condition of Charlie's taxiway which had a slight crack which could result in accidents and incidents. Efforts are being made to improve the performance of AMC unit officers in supporting flight security and safety, namely by minimizing existing human resources so that they can run well and stay focused on the duties of each AMC unit personnel.